Interactions between cannabidiol and Δ9‐tetrahydrocannabinol in modulating seizure susceptibility and survival in a mouse model of Dravet syndrome. (27th July 2020) - Anderson, Lyndsey L.; Low, Ivan K.; McGregor, Iain S.; Arnold, Jonathon C.
Abstract : Background and Purpose: Extracts from the cannabis plant can dramatically improve the health of children suffering from refractory epilepsies such as Dravet syndrome. These extracts typically contain cannabidiol (CBD), a phytocannabinoid with well‐documented anticonvulsant effects, but may also contain Δ 9 ‐tetrahydrocannabinol (Δ 9 ‐THC). It is unclear whether the presence of Δ 9 ‐THC modulates the anticonvulsant efficacy of CBD. Here, we utilized the Scn1a +/− mouse model of Dravet syndrome to examine this question. Experimental Approach: Scn1a +/− mice recapitulate core features of Dravet syndrome, including hyperthermia‐induced seizures, early onset spontaneous seizures and sudden death. We assessed the effects on CBD and Δ 9 ‐THC alone, and in combination on hyperthermia‐induced seizures, spontaneous seizures and premature mortality. Key Results: Administered alone, CBD (100 mg·kg −1 i.p.) was anticonvulsant against hyperthermia‐induced seizures as were low (0.1 and 0.3 mg·kg −1 i.p.) but not higher doses of Δ 9 ‐THC. A subthreshold dose of CBD (12 mg·kg −1 ) enhanced the anticonvulsant effects of Δ 9 ‐THC (0.1 mg·kg −1 ). Sub‐chronic oral administration of Δ 9 ‐THC or CBD alone did not affect spontaneous seizure frequency or mortality while, surprisingly, their co‐administration increased the severity of spontaneous seizures and overall mortality. Conclusion and Implications: Low doses of Δ 9 ‐THC are anticonvulsant against hyperthermia‐induced seizures in Scn1a +/− mice, effects that are enhanced by a sub‐anticonvulsant dose of CBD. However, proconvulsant effects and increased premature mortality are observed when CBD and Δ 9 ‐THC are sub‐chronically dosed in combination. The possible explanations and implications of this are discussed.